Integer composition, connection Appell constants and Bell polynomials - Nataliia Luno (Journal of Numerical Analysis and Approximation Theory, 2021)
We introduce an explicit form of the connection coefficients for Appell polynomial sequences via Toeplitz-Hessenberg matrix determinants.